Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya di PGMI-3 - Widia, Friska; Wandini, Rora Rizki (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Students often find it difficult to solve math problems, this is due to a lack of understanding of the problems presented. So many students experience errors in answering. As happened to PGMI-3 students, who experienced misconceptions when working on mathematics problems, especially on the circumference of flat shapes using Polya Theory. The method used in this research is a descriptive qualitative method. The subjects of this research were PGMI-3 class students. The aim of this research is to describe the forms of misconceptions experienced by students when working on mathematical problems on plane material using Polya Theory. From the research results, it was found that the form of misconception carried out by students was poor perception